Studies of (±)-3,4-Methylenedioxymethamphetamine (MDMA) Metabolism and Disposition in Rats and Mice: Relationship to Neuroprotection and Neurotoxicity Profile - Mueller, Melanie (The American Society for Pharmacology and Experimental Therapeutics, 2013)
The neurotoxicity of (±)-3,4-methylenedioxymethamphetamine (MDMA; “Ecstasy”) is influenced by temperature and varies according to species. The mechanisms underlying these two features of MDMA neurotoxicity are unknown, but differences in MDMA metabolism have recently been implicated in both. The present study was designed to 1) assess the effect of hypothermia on MDMA metabolism, 2) determine whether the neuroprotective effect of hypothermia is related to inhibition of MDMA metabolism, and 3) determine if different neurotoxicity profiles in mice and rats are related to differences in MDMA metabolism and/or disposition in the two species. Rats and mice received single neurotoxic oral doses of MDMA at 25°C and 4°C, and body temperature, pharmacokinetic parameters, and serotonergic and dopaminergic neuronal markers were measured. Hypothermia did not alter MDMA metabolism in rats and only modestly inhibited MDMA metabolism in mice; however, it afforded complete neuroprotection in both species. Rats and mice metabolized MDMA in a similar pattern, with 3,4-methylenedioxyamphetamine being the major metabolite, followed by 4-hydroxy-3-methoxymethamphetamine and 3,4-dihydroxymethamphetamine, respectively. Differences between MDMA pharmacokinetics in rats and mice, including faster elimination in mice, did not account for the different profile of MDMA neurotoxicity in the two species. Taken together, the results of these studies indicate that inhibition of MDMA metabolism is not responsible for the neuroprotective effect of hypothermia in rodents, and that different neurotoxicity profiles in rats and mice are not readily explained by differences in MDMA metabolism or disposition.